Sistemas urbanos de água: avaliação de método para análise de sustentabilidade ambiental de projetos - Figueiredo, Glauco Antônio Bologna Garcia de (Universidade Federal de São Carlos, 2002)
The sustainable development concept has been used as a basic framework of urban planning processes. Due to its subjective components there were cases where the sustainability principles were used as marketing instruments, instead of an objective planning tool. As an attempt to reverse this situation the group for Sustainable and Strategic Urban Planning, from the São Carlos Federal University, studies way to apply sustainable development principles in the assessment and analysis of urban projects. In this thesis it was created a Method, which can be used in the evaluation of components of urban water system projects (water supply, wastewater collection and treatment, urban drainage, etc.). The Method is based on defined parameters and uses descriptive lists, flowcharts and interaction matrices to indicate sustainability tendencies (positive, negative or neutral). This model was applied in five different projects, which indicated some adjustments. The model was considered simple and effective. Another advantage of the Method is its modular character: new information and tools can be added, in order to obtain more complex analysis. Besides that, it can be used to evaluate the planning or performance of other sustainable systems.
Keywords: Engenharia sanitária; Sustentabilidade; Desenvolvimento sustentável; Água sistemas urbanos; Projetos avaliação; Sustainability; Sustainable development; Basic sanitation; Urban water system; Evaluation of Projects; ENGENHARIAS::ENGENHARIA SANITARIA